Individualism, Competitiveness, and Fear of Negative Evaluation in Pre-adolescents: Does the Teacher’s Controlling Style Matter? - Salazar-Ayala, Carla Mariela; Gastélum-Cuadras, Gabriel; Huéscar Hernández, Elisa; Núñez Enríquez, Oscar; Barrón Luján, Juan Cristóbal; Moreno-Murcia, Juan Antonio (Frontiers in Psychology, 2021)
The purpose of this study was to examine, the relationship between teacher's controlling motivational style perceived by the students and student's perceived fear of negative evaluation, mediated by the frustration of psychological needs, motivation, and individualism/competitiveness, through the theoretical framework of Self-Determination Theory (SDT, Deci and Ryan, 1985, 2000). Participants 1132 students from fifth and sixth grade in public elementary schools in the State of Chihuahua, Mexico, between the ages of 10 and 13 (M = 10.51 years; SD = .66 years). Results indicated the perceived controlling teaching style positively predicted the fear of negative evaluation in students of this study, through the basic psychological needs frustration, that were positively related to low-quality motivation, which are related to a higher level of individualism/competitiveness, this in turn has proof to be a predictor of fear to negative evaluation. The results also discussed, the promotion of the autonomy support style avoiding the teaching controlling style, for the minimization of negative results related to the perception of fear and the development of student's well-being, both within and beyond the school context.